Mathematic Method To Improve The Parameters Of Electric Power Transmission Lines - Chaaban, Faisal; Husam Aldin, Alaa Aldin (Latakia University Journal -Engineering Sciences Series, 2019)
بعد التطور الكبير الذي شهده قطرنا العربي السوري في مجال توليد الطاقة الكهربائية دعت الحاجة إلى التوسع بشبكات النقل بتوترات عالية لتواكب التوسع الكبير في المشاريع الخدمية والزراعية والصناعية والتجارية . لكن النقل بتوترات عالية يترتب عليه آثار سلبية عديدة على البيئة والوسط الخارجي . في بحثنا تم معالجة إمكانية زيادة قدرة الشبكات الكهربائية في نقل الطاقة الكهربائية دون الحاجة لرفع سوية التوتر الاسمي ، وذلك من خلال زيادة قيمة التيار المسموح بنقله في خطوط النقل انطلاقاً من التأثير على بارامترات الخط الرئيسية و المتمثلة بالممانعة التحريضية و الناقلية السعوية بدون استخدام أية وسائل إضافية (وسائل تعويض الاستطاعة الردية ، وسائل تنظيم التوتر ). النتائج بينت إمكانية تقليل الممانعة الردية وزيادة الناقلية السعوية في خط أحادي الدارة من خلال زيادة عدد النواقل في الطور الواحد و تقليص المسافة الفاصلة بين نواقل الأطوار المختلفة إلى الحد الذي تسمح به شروط الكورونا والتوترات الزائدة ، أما في الخطوط ثنائية الدارة فقد تم بلوغ النتيجة السابقة من خلال تغيير زاوية الانزياح بين أطوار الدارات المختلفة بالإضافة للعوامل السابقة . وهذا يؤدي إلى تحسين قدرة الخط على نقل الاستطاعة الفعلية للمستهلك بدون الحاجة إلى رفع توتر النقل وبالتالي تفادي التكاليف المادية الكبيرة والأضرار الاجتماعية المتمثلة في ملكية الأراضي الزراعية الواقعة في حرم خطوط التوتر العالي . After the great development in Syrian Arab Republic in the field Electric of power generation there is a need to extend the high voltage transmission networks to suit the extended growing in service projects and industrial and commercial projects . But the transmission through high voltage networks have many negative effects on the environment . In our research we developed the ability of increasing the capability of networks to transmit the power without the need to increase the nominal voltage through increasing the value of permissible current transmitted by the transmission lines . this arrangement can be done by the effect on the main line parameters which are represented by the inductive impedance and conductive capacitance without using any additional equipments ( reactive power compensation equipments , equipments of voltage control ) . The results showed the ability of decreasing the inductive impedance and increasing the conductive capacitance through increasing the number of conductors in the phase and decreasing the distance between conductors of the different phases to level which is allowed by corona, in addition to the control of shifting angle between the radial values of phases voltages or current of the different circuits .This lead to improve the capability of the line to transmit the active power to customers , without need to increase transmission voltage , and then avoid the great cost and social damage represented by the own of agrarian lands in the area of high voltage lines path.